Effects of different passivators and vermicomposting on fractionations of copper and zinc in pig manure - ZHANG Wei; SHI Jiachun (浙江大学学报. 农业与生命科学版)
With the development of intensive livestock farming, a large number of heavy metals such as copper (Cu) and zinc (Zn) are widely used in feed. However, the accumulations of heavy metals in animal manures have become serious environmental problems, which may even pose long-term threats to ecosystems and humans.This study focused on the effects of different passivators and vermicomposting on fractionations of heavy metals (Cu and Zn) and their bioavailability during pig manure vermicomposting. In the plot experiment treatments, calcium-magnesium phosphate, bentonite, biochar, enzymes, EM bacteria, fly ash and zeolite were added to the pig manure as heavy metal passivators, while vermicomposting treatment without passivator was set as a control.The results indicated that the biochar, enzymes, EM bacteria, fly ash and zeolite treatments had a passivation effect on Cu fractionation. Meanwhile, the bioavailable Cu was converted into immobilized Cu, and there was a significant difference between the treatment group and the control (P<0.05). In terms of the distribution rates of available Cu and Zn, biochar was considered as the best passivator for available Cu with up to 42.34% reduction of the distribution rate, and enzymes were considered as the best passivator for available Zn (P<0.05) with a maximum reduction (3.77%) of the distribution rate. The concentrations of various Cu forms in each fraction for the pig manure vermicompost were in the order of oxidizable Cu>residual Cu>reducible Cu>exchangeable Cu, while the concentrations of various Zn forms represented in the order of exchangeable Zn>reducible Zn>oxidizable Zn>residual Zn. Oxidizable Cu was the dominant speciation for Cu with a fraction up to 50%, while the exchangeable and reducible Zn were the dominant speciations for Zn (>80%) in the pig manure vermicompost. Based on the Community Bureau of Reference (BCR) sequential speciation analysis, the bioavailability of Cu and Zn decreased after vermicomposting. The effect of passivators was different on the bioavailability of Cu and Zn, which showed that Zn was mostly available while Cu was mostly unavailable to plants after vermicomposting. Therefore, more attention should be paid to the risk of environmental pollution caused by Zn in compost application.In conclusion, this research provides theoretical and technical information on vermicomposting of pig manure, which is of great significance to pollution prevention and risk management for heavy metals.